Identification and validation of novel prognostic biomarkers and therapeutic targets for non-small cell lung cancer - Lai, Li-Ting; Ren, Yuan-Hui; Huai, Ya-Jun; Liu, Yu; Liu, Ying; Wang, Shan-Shan; Mei, Jin-Hong (Frontiers in Genetics, 2023)
Background: Despite the significant survival benefits of anti-PD-1/PD-L1 immunotherapy, non-small cell lung cancer (NSCLC) remains one of the most common tumors and major causes of cancer-related deaths worldwide. Thus, there is an urgent need to identify new therapeutic targets for this refractory disease. Methods: In this study, microarray datasets GSE27262, GSE75037, GSE102287 and GSE21933 were integrated by Venn diagram. We performed functional clustering and pathway enrichment analyses using R. Through the STRING database and Cytoscape, we conducted protein-protein interaction (PPI) network analysis and identified the key genes, which were verified by the GEPIA2 and UALCAN portal. Validation of actin-binding protein anillin (ANLN) was performed by quantitative real time polymerase chain reaction and western blotting. Additionally, Kaplan-Meier methods were used to compute the survival analyses. Results: In total, 126 differentially expressed genes were identified, which were enriched in mitotic nuclear division, mitotic cell cycle G2/M transition, vasculogenesis, spindle, and peroxisome proliferator-activated receptor signaling pathway. 12 central node genes were identified in the PPI network complex. The survival analysis revealed that high transcriptional levels were associated with inferior survival in NSCLC patients. The clinical implication of ANLN was further explored; its protein expression showed a gradually increasing trend from grade I to III. Conclusions: These Key genes may be involved in the carcinogenesis and progression of NSCLC, which may serve as useful targets for NSCLC diagnosis and treatment.